El ñandú (Rhea americana) y su extinción en libertad en la provincia de Buenos Aires - Carman, Raúl Leonardo (1983)
The Nandú (Rhea americana) and its extinetion in the wiId in the Province of Buenos Aires. In this paper, it is shown that in the second half of the XIX century; the Ñandú (Rhea americana ) was a scarce bird in the area of the Province of Buenos Aires. The hunting practiced by the indians and the gauchos is mentioned as the chief cause for the decreasing number of tbe specie during the XIX century, the destruction of eggs being included in the term hunting. The changes occurred in tbe natural surroundings of the Province of Buenos Aires during the last hundred years also contributed to the extinction of this bird in the wild. The autbor mentions the main natural enemies of the Rhea. The reasons for its hunting are also referred to the entertainment or amusement provided by its capture and the use of its feathers and skin. A description is given of the throwing weapon used for ¡ts capture by the inhabitants of the pampas during the lalt century.